Nano Hybrids and Composites Vol. 33 - Al-Ahmed, Amir; Kim, Yun-Hae (Nano Hybrids and Composites, 2021)
The 33rd volume of the Nano Hybrids and Composites journal presents new research results in the area of fabrication and characterization of new composite materials and graphene nanostructures. Papers are devoted to the study of the biopolymer properties, the effect of physical aging on the polylactic acid, the dynamic behavior of nanoplates, the investigation of the polymer application in the photoconductive detectors, and vibration analysis of nanobeam. The journal will be of interest to both researchers in the field of nanomaterials and university professors and lecturers. Nanocomposite, silver nanoparticles, silica, graphene, nanostructures, advanced materials, nanobeam, nanoplate, physical aging, mechanical properties, thermal conductivity, biopolymer. Materials Science, Nanoscience.